The changing structure of the Nigerian economy - Central Bank of Nigeria; Mordi, Charles N. O.; Englama, Abwaku; Adebusuyi, Banji S.; Central Bank of Nigeria (Abuja : Central Bank of Nigeria, 2010)
This book evaluates the general effects of the economic development strategies and policies which have been adopted by the various administrations, on the structure of the Nigerian economy since her polictical independence in 1960.
Includes bibliographical references
osc 13/09/2013
Loans
Keywords: Economic Conditions; Changing structure; Economy policy; Nigeria